Modern methods of IT technologies in the educational process for bachelors - Nurkasymova Сауле (Рroblems of engineering and professional education, 2023)
Technological design is considered as the quality of teaching, manifested in the form of its ability and readiness for the educational process. The concept of "technology" in modern pedagogy is not sufficiently established to express the high professionalism and qualifications of a specialist.